CyclinD1 Down‐Regulation and Increased Apoptosis Are Common Features of Cohesinopathies. Issue 3 (23rd November 2015) - Fazio, Grazia; Gaston‐Massuet, Carles; Bettini, Laura Rachele; Graziola, Federica; Scagliotti, Valeria; Cereda, Anna; Ferrari, Luca; Mazzola, Mara; Cazzaniga, Gianni; Giordano, Antonio; Cotelli, Franco; Bellipanni, Gianfranco; et al.
Abstract : Genetic variants within components of the cohesin complex ( NIPBL, SMC1A, SMC3, RAD21, PDS5, ESCO2, HDAC8 ) are believed to be responsible for a spectrum of human syndromes known as "cohesinopathies" that includes Cornelia de Lange Syndrome (CdLS). CdLS is a multiple malformation syndrome affecting almost any organ and causing severe developmental delay. Cohesinopathies seem to be caused by dysregulation of specific developmental pathways downstream of mutations in cohesin components. However, it is still unclear how mutations in different components of the cohesin complex affect the output of gene regulation. In this study, zebrafish embryos and SMC1A ‐mutated patient‐derived fibroblasts were used to analyze abnormalities induced by SMC1A loss of function. We show that the knockdown of smc1a in zebrafish impairs neural development, increases apoptosis, and specifically down‐regulates Ccnd1 levels. The same down‐regulation of cohesin targets is observed in SMC1A ‐mutated patient fibroblasts. Previously, we have demonstrated that haploinsufficiency of NIPBL produces similar effects in zebrafish and in patients fibroblasts indicating a possible common feature for neurological defects and mental retardation in cohesinopathies. Interestingly, expression analysis of Smc1a and Nipbl in developing mouse embryos reveals a specific pattern in the hindbrain, suggesting a role for cohesins in neural development in vertebrates. J. Cell. Physiol. 231: 613–622, 2016. © 2015 Wiley Periodicals, Inc.